Workplace mobbing and organizational intelligence - healthcare risk management in a crisis. (20th October 2021) - Dimitrova, D
Abstract: Issue: Mobbing is the old syndrome of the new age. A phenomenon of invisible systemic group pressure on a selected dissident victim and a visible harassment that sticks strongly in a crisis. A victim with a strong character, a person competent and leadership skills to a degree that exceeds another placed leader, as an expression of his fear and frustration. The presence of mobbing is always an expression of a bad organizational culture. The opportunities for risk reduction are based in the creation of a highly effective, tactical-strategic flexibility and creative program of control, mediation and modeling of the risk factors leading to mobbing. Description of the problem: A particularly interesting scene for the manifestation of mobbing is the academic environment. The manifestation of mobbing leads to serious losses, social isolation and has health consequences on the attacked and subjected to emotional pressure member of the team. A creative scientist and charismatic teacher, a wonderful and eroded specialist does not go unnoticed by the more mediocre. Circles are formed with different scope and degrees of trust in the initiator of the mobbing, who generates and manages directly several with the role of accomplices and indirectly dozens to hundreds of cowardly and sufficiently obedient performers. Results: Basic human rights are violated and the organizational culture of the institution is compromised through mobbing. A process of a cyclical nature in which only the victim changes. The implementation of a policy of zero tolerance for mobbing is a starting point, but it is not enough for a lasting solution to a problem with the volume and nature of a socio-economic disaster. Lessons: Mobbing is a conflict of interest in which the better prepared fall victim to the more mediocre. Insufficiently good level of management at all levels in the institution leads to mobbing when a competent and eroded member of the team appears. Key messages: No one is protected from mobbing in bad and destructive management. A mobbing risk reduction program is applicable to each prevention indication at each level.